Review of the Clinical Types of Dermatophytes - Numan, Rand Salwan; Farhan, Mohammed Sami; Abdullah, Bilal Ahmed; Mamdwooh, Ali Esam; Abdulla, Sara Najim (Journal for Research in Applied Sciences and Biotechnology, 2024)
Fungi known as dermatophytes require keratin in order to develop. "Ringworm" is the common term for superficial fungus infections that affect the skin's keratinized layers and its limbs in both humans and animals. These fungi have the potential to superficially infect nails, hair, and skin. Ringworm fungi have the ability to penetrate all layers of skin. Dermatophytes can be transmitted directly by people (anthropophilic organisms), indirectly by fomites, and by animals (zoophilic organisms), soil (geophilic organisms), and other people. Dermatophytes are the cause of the medical condition known as dermatophytosis. Approximately 25% of the global population suffers from dermatophytosis, and no human population is immune to these mycotic disorders. There are three genera in total. the more than twenty species of dermatophytes: Trichophyton, Microsporum, and Epidermophyton. By providing reliable epidemiological data, it is imperative that we expand broaden public knowledge of the importance of these illnesses and deepen our understanding of fungal biology and pathology. Ecological classifications, clinical potential for pathogenicity manifestations, and "chemical and natural" dermatophytosis therapy alternatives are some of the review themes.